Expert consensus on imaging diagnosis of acquired immunodeficiency syndrome associated pneumocystis jirovecii pneumonia - Radiology Committee on Infectious and Inflammatory Disease; Chinese Research Hospital Association; Infectious Diseases Sub-branch; Radiology Branch; Chinese Medical Association; Beijing Imaging Technology Innovation Alliance (Yixue xinzhi zazhi)
Pneumocystis jirovecii pneumonia (PJP) is a worldwide opportunistic infection disease. Imaging technology had proven to be very useful in early detecting, evaluating and surveillance on chemotherapy. In order to promote the diagnosis and treatment of acquired immunodeficiency syndrome (AIDS) associated PJP in China can be worked correctly, effectively, safely and widely, the expert group used the methodological requirements of evidence-based medicine for guidelines and standards, to formulate the imaging diagnostic criteria for AIDS associated PJP. This standard is based on the latest research evidence, considering the clinical practice and imaging experience, so as to provide clear diagnostic criteria and guide the reasonable and comprehensive treatment for this disease.